The repeated procedure PRMZSS1 for estimating the polynomial zeros simultaneously - Monsi, Mansor; Hassan, Nasruddin; Mohammad Rusli, Syaida Fadhilah (Institute for Mathematical Research, Universiti Putra Malaysia, 2016)
Our previous method that is PMZSS1 has a rate of convergence of at least eight. The aim of repeating the steps in PMZSS1 is to yield a better rate of convergence. The resulting method is called the repeated midpoint zoro PRMZSS1 where its rate of convergence is at least 7r +1 with r ≥ 1.The proof of this result is detailed in the convergence analysis of PRMZSS1. Numerical results and comparison with the existing procedures of PZSS1 and PMZSS1 are included to confirm our theoretical results, where the rate of convergence of PZSS1 and PMZSS1 are four and eight respectively.